PERLAKUAN AKUNTANSI ASET TETAP PADA BAZNAS KOTA BUKITTINGGI BERDASARKAN PSAK NO. 16 - Renold Muhammad; Nini Sumarni; Novera Martilova; Yenty Astari Dewi (Universitas Logistik dan Bisnis Internasional, 2026)
BAZNAS Bukittinggi city owns several fixed assets that are damaged and no longer used in institutional activities. Under PSAK No. 16, such assets should be derecognized. This study uses a descriptive qualitative method by analyzing financial reports related to fixed asset records, with data drawn from primary and secondary sources. The findings show that BAZNAS has implemented PSAK No. 16 in terms of recognition, acquisition, depreciation, and reporting. However, derecognition has not been applied, causing acquisition costs of damaged assets to remain in the financial statements. This results in losses on asset derecognition, which should be presented in the statement of changes in funds. According to BAZNAS and LAZ financial policies, differences arising from asset disposal must be reported in the financial statements under amil funds, zakat funds, or infak and sedekah funds.